2021
DOI: 10.1590/1518-8345.5104.3485
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and its influence on maternal breastfeeding self-efficacy

Abstract: Objective: to identify the levels of anxiety and breastfeeding self-efficacy in puerperal women at the intervals of 60, 120, and 180 days postpartum; and to verify the influence of anxiety on breastfeeding self-efficacy among these puerperal women. Method: an analytical, longitudinal and prospective study, conducted with 186 puerperal women, and which used a sociodemographic and obstetric characterization questionnaire, the State-Trait Anxiety Inventory, and the Breastfeeding Self-Efficacy Scale - Short Form.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Demonstrated reliability and validity [ 31 ] 0.70 The State Anxiety Inventory Form Y-1 (STAI-S) [ 32 ] 20 items, 4-point Likert scales ranging from 1 (almost never) to 4 (almost always), range 20–80, a higher score denoting a high anxiety level. Demonstrated reliability and validity [ 33 ] 0.93 Section 3 COVID-19 Vaccination Acceptability Tools [ 34 ] Part 1: 27 items (24 items about a possible COVID-19 vaccination and added 3 items on BF-related COVID-19), eleven-point scale (0–10) from "strongly disagree" to "strongly agree", range 0–270, higher scores denoting a more positive attitude Part 2: 1 item of vaccination intention, eleven-point scale (0–10) from "very unlikely" to "very likely", range 0–10, higher scores denoting higher intention for COVID-19 vaccination Demonstrated reliability and validity [ 34 ] 0.82 The Exclusive Breastfeeding Social Support Scale (EBFSS scale) [ 35 ] 16 items (assessed 3-domains of family support; emotional, informational, and instrumental support), 3-point Likert scales, ranging from 1 (no help at all), 2 (less than you would like), and 3 (as much as you would like), range 16–48, a higher score indicating stronger support for EBF. Demonstrated reliability and validity [ 35 ] 0.90 The Health Provider Support in Breastfeeding during COVID-19 (HSBF-COVID scale) [ 13 , 36 39 ] 15 items (assessed 4-domains of healthcare support; emotional, informational, instrumental, and appraisal support), 3-point Likert scales ranging from 1 (no help at all), 2 (less than you would like), and 3 (as much as you would like), range 15–45, higher scores indicating a higher level of health provider support for BF during pandemic 0.92 …”
Section: Methodsmentioning
confidence: 99%
“…Demonstrated reliability and validity [ 31 ] 0.70 The State Anxiety Inventory Form Y-1 (STAI-S) [ 32 ] 20 items, 4-point Likert scales ranging from 1 (almost never) to 4 (almost always), range 20–80, a higher score denoting a high anxiety level. Demonstrated reliability and validity [ 33 ] 0.93 Section 3 COVID-19 Vaccination Acceptability Tools [ 34 ] Part 1: 27 items (24 items about a possible COVID-19 vaccination and added 3 items on BF-related COVID-19), eleven-point scale (0–10) from "strongly disagree" to "strongly agree", range 0–270, higher scores denoting a more positive attitude Part 2: 1 item of vaccination intention, eleven-point scale (0–10) from "very unlikely" to "very likely", range 0–10, higher scores denoting higher intention for COVID-19 vaccination Demonstrated reliability and validity [ 34 ] 0.82 The Exclusive Breastfeeding Social Support Scale (EBFSS scale) [ 35 ] 16 items (assessed 3-domains of family support; emotional, informational, and instrumental support), 3-point Likert scales, ranging from 1 (no help at all), 2 (less than you would like), and 3 (as much as you would like), range 16–48, a higher score indicating stronger support for EBF. Demonstrated reliability and validity [ 35 ] 0.90 The Health Provider Support in Breastfeeding during COVID-19 (HSBF-COVID scale) [ 13 , 36 39 ] 15 items (assessed 4-domains of healthcare support; emotional, informational, instrumental, and appraisal support), 3-point Likert scales ranging from 1 (no help at all), 2 (less than you would like), and 3 (as much as you would like), range 15–45, higher scores indicating a higher level of health provider support for BF during pandemic 0.92 …”
Section: Methodsmentioning
confidence: 99%
“…Similarly, in studies conducted in the literature, a negative relationship was found between self-efficacy and postpartum anxiety in puerperae (Dol et al, 2021; Feligreras-Alcalá et al, 2020; Razurel et al, 2017; Reck et al, 2012). Having an adequate level of self-efficacy in the postpartum period not only affects the mother’s own mental health positively but also has a positive impact on breastfeeding, baby care, and the baby’s psychological development (Abuhammad, 2020; Melo et al, 2021; Sari & Altay, 2020). Therefore, lack of both self-efficacy and high anxiety will cause the mother not to enjoy the postpartum period and create obstacles to establishing a quality relationship with her baby.…”
Section: Discussionmentioning
confidence: 99%
“…Perceived self-efficacy is the individual’s belief in his or her capacity to organize the required actions and implement them to achieve a task. It represents the individual’s confidence in themselves (Melo et al, 2021). Powerful mother self-efficacy perceptions appear to be associated with lower anxiety (Law et al, 2019; Melo et al, 2021).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…From a mechanistic perspective, anxiety may interfere with milk production and ejection via elevations in cortisol, increased insulin resistance and reduced oxytocin release (Nagel et al, 2022), and can also impair a mother's sense of self-efficacy, leading to a loss of confidence in her ability to sustain breastfeeding over time (Corby et al, 2021;Melo et al, 2021). Anxiety during pregnancy has been linked to a lower likelihood of initiating breastfeeding (English et al, 2020), a shorter duration of breastfeeding (Riedstra and Aubuchon-Endsley, 2019;Stuebe et al, 2019), and an earlier introduction of formula feeds (Stuebe et al, 2019).…”
Section: Relationship Between Mental Health Variables and Breastfeedingmentioning
confidence: 99%